Bản sắc nghề nghiệp của hiệu trưởng: Nghiên cứu trường hợp tại một trường tiểu học và trung học cơ sở dựa trên lí thuyết phát triển bản sắc của Burke và Stets - Trần Tuyết Oanh, Trần Tuyết Oanh; Phạm Thị Hương, Phạm Thị Hương (Tạp chí Giáo dục, 2026)
The professional identity of school principals is increasingly recognized as a critical factor directly influencing leadership behaviors and practices within schools. This study explores the development of a principal’s professional identity within a school context. Drawing upon the identity theory of Burke and Stets(2009), the research employs a qualitative methodology, conducting interviews with one principal and eight teachers at a combined elementary and middle school in Ho Chi Minh City. Data analysis identifies four key facets of Principal Tien’s professional identity: a fair, equity-oriented, benevolent, and compliant principal. These identities often exhibit internal contradictions and mutual conflicts, particularly between benevolence and compliance, which somehow impact his leadership decision-making process. Consequently, the study emphasizes the necessity of developing the capacity to identify and regulate identity conflicts within principal training and professional development programs.